2021
DOI: 10.31557/apjcp.2021.22.11.3493
|View full text |Cite
|
Sign up to set email alerts
|

Determination of β-catenin Expression in Breast Cancer and Its Relationship with Clinicopathologic Parameters

Abstract: Background: Abnormal activation of the β-catenin signaling pathway is involved in various malignancies, including breast carcinoma.Aberrant expression of β-catenin has been associated with more aggressive behaviors of breast cancer in some previous studies. . In the present study, we intend to evaluate the β-catenin expression in breast cancer specimens and study its relationship with clinicopathological parameters. Materials and method: In this crosssectional study,88 samples diagnosed as invasive ductal brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Phosphorylation of IRS-1 stimulates PI3K/Akt signaling that plays a pivotal role in cell proliferation, cell survival, migration, and differentiation [66]. Inappropriate activation of PI3K/Akt signaling has been reported in diverse malignancies including breast cancer [67][68][69]. Our findings indicate that in obese breast tumors, PI3K stimulates PDK1, which phosphorylates Akt kinase.…”
Section: Discussionsupporting
confidence: 57%
“…Phosphorylation of IRS-1 stimulates PI3K/Akt signaling that plays a pivotal role in cell proliferation, cell survival, migration, and differentiation [66]. Inappropriate activation of PI3K/Akt signaling has been reported in diverse malignancies including breast cancer [67][68][69]. Our findings indicate that in obese breast tumors, PI3K stimulates PDK1, which phosphorylates Akt kinase.…”
Section: Discussionsupporting
confidence: 57%
“…In gastric cancer cells, overexpression of HER2 was shown to increase the stemness and invasiveness, which is regulated by Wnt/β-catenin signaling (Jung et al, 2019). Previously the aberrant expression of β-catenin was associated with more aggressive behaviors of BC although it was not statistically correlated to HER2 (Sefidbakht et al, 2021). However, in epithelial ovarian cancer (EOC), high expression of β-catenin was found in HER2-positive EOC tissue samples and was correlated with a poor patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Wnt/β-catenin signaling pathway is abnormally activated in human cancers, including BC (Brennan & Brown, 2004;Song et al, 2016). Alternation of β-catenin expression may result from mutation and amplification, both of them lead to the occurrence and progression of BC (Sefidbakht et al, 2021;Zhang et al, 2021). Because β-catenin plays an important role in the formation and metastasis of tumor formation, small molecule inhibitors that target β-catenin are being developed to suppress tumor progression (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Aberrant activation of β-catenin has been observed in metastatic breast cancer and is associated with increased tumor aggressiveness and metastatic potential. 26,27 Although YAP and β-catenin both contribute to the cellular mechanotransduction, their interaction and synergistic effects in breast cancer metastasis remains unclear. It has been shown that YAP is a component of the β-catenin destruction complex, and YAP is sequestered in the cytoplasm to interact with the destruction complex.…”
mentioning
confidence: 99%